Moderasi Beragama dalam Bingkai Kearifan Lokal: Studi Suku Tidung di Nunukan - Fitriono, Eko Nani; Husnul Khatimah; Melisa Titin Usmawati; Nurhalisa; Siti Sarmila Angraini (Rayah Al-Islam, 2024)
This research aims to find out how religious moderation is an understanding that already exists in the Tidung Tribe through the culture they have traditions in everyday life, which through this tradition is in line with the aim of moderation, namely respect for differences and understanding differences within a frame of harmony. This research is field research with an ethnographic approach. Through an ethnographic approach, the researcher wants to take a closer picture of the culture of the Tidung Tribe and the values ​​of moderation resulting from the existing culture, both through direct observation and interviews in finding research results. The research findings show that the Tidung Tribe continues to strive to maintain their identity and cultural diversity while remaining open to change and progress over time. Through the spirit of mutual cooperation and togetherness, the Tidung Tribe seeks to strengthen national unity and unity, as well as maintain harmony between tribes and ethnicities in the Nunukan region, North Kalimantan. On the other hand, the culture of the Tidung Tribe, like the Iraw, is interpreted as not just a ceremony, but an effort to honor and celebrate together, as well as recognizing differences. In this case, the Tidung Tribe shows that harmony between religious communities can be strengthened through dialogue and cooperation.